Power of 2000

Algebra Level 4

( 1 + 1 x ) x + 1 = ( 1 + 1 2000 ) 2000 \large \left(1+\frac{1}{x}\right)^{x+1}=\left(1+\frac{1}{2000}\right)^{2000}

Given that x x is an integer that satisfies the equation above, find the value of x x .


The answer is -2001.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Michael Mendrin
Sep 23, 2014

Let y = x 1 y=-x-1 and we plug that into

( 1 + 1 y ) y + 1 { \left( 1+\dfrac { 1 }{ y } \right) }^{ y+1 }

( 1 1 x + 1 ) x { \left( 1-\dfrac { 1 }{ x+1 } \right) }^{- x }

( x x + 1 ) x { \left( \dfrac { x }{ x+1 } \right) }^{ -x }

( x + 1 x ) x { \left( \dfrac { x+1 }{ x } \right) }^{ x }

( 1 + 1 x ) x { \left( 1+\dfrac { 1 }{ x } \right) }^{ x }

Hmm….

hahaha I like your solution. Especially the "Hmm..." part!

Dieuler Oliveira - 6 years, 8 months ago

Nice solution.. Upvoted :)

Hrishik Mukherjee - 6 years, 4 months ago

I'm new here and I haven't been posting my solutions because my LaTeX does not show up correctly for some odd reasons. It was so garbled here that I deleted it. And now I am unable to try again. Here is how I solved this.

Solution Solution

Oyekola Oyekole - 6 years, 4 months ago

Hmm....if that is the case; what is the value of x then?

Jun Ab's - 6 years, 4 months ago
Oyekola Oyekole
Feb 4, 2015

We will manipulate the LHS until it has the form of the RHS L H S = ( 1 + 1 x ) x + 1 = ( x + 1 x ) x + 1 LHS = \left ( 1+ \frac{1}{x} \right )^{x+1} = \left(\frac{x+1}{x}\right)^{x+1} while R H S = ( 1 + 1 2000 ) 2000 = ( 2001 2000 ) 2000 RHS = \left (1 + \frac{1}{2000}\right )^{2000} = \left(\frac{2001}{2000}\right)^{2000}

LHS is not yet in the RHS form because the denominator must equal the power, and each must be one less than the numerator. So we manipulate LHS.

L H S = ( x + 1 x ) x + 1 = ( 1 x + 1 x ) ( x + 1 ) = ( x x + 1 ) ( x + 1 ) LHS = \left (\frac{x+1}{x}\right )^{x+1} \\ = \left (\frac{1}{\frac{x+1}{x}}\right )^{- \left(x+1\right)} = \left(\frac{x}{x+1}\right)^{-\left(x+1\right)}

We manipulate the fraction in the LHS further, multiplying numerator and denominator by -1 so that the denominator and the power are equal, as it is in the RHS

L H S = ( x ( x + 1 ) ) ( x + 1 ) = ( x x 1 ) x 1 LHS = \left(\frac{-x}{-\left(x+1\right)}\right)^{-\left(x+1\right)} = \left(\frac{-x}{-x-1}\right)^{-x-1}

Finally we can compare with the RHS and get x 1 = 2000 -x-1 = 2000

x = 2001 \Rightarrow x = -2001

As mentioned in your note, I have undeleted your solution and edited it. If you do not want this, please delete it again.

Calvin Lin Staff - 6 years, 4 months ago

Log in to reply

Thanks Calvin

Oyekola Oyekole - 6 years, 4 months ago
Harshit Singhania
May 19, 2015

(1+1/x)^(x+1)=(1+1/2000)^2000

>>> ((x+1)/x)^(x+1)=(2001/2000)^2000 Now you notice that if x=2000 then the numerator would be the same as the RHS numerator but the power won't be, but on taking -2001 the equation will hold ((-2001+1)/-2001)^-2001+1 =( -2000/-2001)^-2000 = ((2000/2001)^(-1))^2000 =(2001/2000)^2000 =RHS

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...